Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1124/jpet.114.218156
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced S-Nitrosylation of Soluble Guanylyl Cyclase and Expression of Phosphodiesterase 1A Contribute to Dysfunction of Longitudinal Smooth Muscle Relaxation

Abstract: The effect of proinflammatory cytokines on the expression and activity of soluble guanylyl cyclase (sGC) and cGMP-phosphodiesterases (PDEs) was determined in intestinal longitudinal smooth muscle. In control muscle cells, cGMP levels are regulated via activation of sGC and PDE5; the activity of the latter is regulated via feedback phosphorylation by cGMP-dependent protein kinase. In muscle cells isolated from muscle strips cultured with interleukin-1b (IL-1b) or tumor necrosis factor a (TNF-a) or obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Decreased basal tone and, thus, a larger resting diameter of the distal colon compromised the ability of smooth muscles to further relax. Similar findings have been observed following intestinal inflammation where smooth muscle relaxation in response to a NO donor was decreased (Van Bergeijk et al, ; Rajagopal et al, ). This compromised ability to relax was in part attributed to iNOS‐mediated protein nitrosylation (Rajagopal et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Decreased basal tone and, thus, a larger resting diameter of the distal colon compromised the ability of smooth muscles to further relax. Similar findings have been observed following intestinal inflammation where smooth muscle relaxation in response to a NO donor was decreased (Van Bergeijk et al, ; Rajagopal et al, ). This compromised ability to relax was in part attributed to iNOS‐mediated protein nitrosylation (Rajagopal et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Toward this end, the PDE5selective inhibitors, sildenafil, tadalafil, and MY5445, enhanced intracellular cGMP/PKG signaling, which correlated with abated cancer cell proliferation and increased apoptosis (145). Interestingly, cytokine-induced NOS2 led to Snitrosylation and inhibition of sGC activity, as well as reduced formation of cGMP and increased PDE1 in smooth muscle cells (110). These results suggest that high-flux NO derived from NOS2 abates cGMP signaling through S-nitrosylation and PDE mechanisms.…”
Section: No and Cgmp Signalingmentioning
confidence: 94%
“…Oxidized sCG is presumably present in several diseased vessels (Beuve, 2017). However, while reduced response to NO, nitroprusside and/or sGC stimulators associated with sGC S‐nitrosylation has been reported following exposure to pathological stimuli including angiotensin II, aldosterone, IL‐1β or TNF‐α (Choi et al, 2011; Crassous et al, 2012; Maron et al, 2009; Rajagopal et al, 2015), increased response to sGC activators has not been shown. sGC oxidation associated with a reduced response to NO, NO donors or sGC stimulators with concomitant increased response to sGC activators has only been shown so far in artificial systems by oxidizing agents (Tawa et al, 2019) or in genetically modified animals such as the heme‐deficient sGC mice (Thoonen et al, 2015) or the CYB5R3−/− mice (Rahaman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%